Perbedaan Sikap Partai Koalisi dalam Pengisian Sisa Masa Jabatan Wakil Bupati Ende Periode 2018-2023 - Helenerius Ajo Leda (LITERATUS, 2022)
The This study highlights the problem of differences in attitudes at the coalition party level in responding to the discourse of filling the remaining term of office of the Deputy Regent of Ende for the 2018-2023 period. This difference in attitude has led to divisions within the coalition parties, which are converging on two opposite poles, namely Golkar on the one hand and PDIP, Nasdem, Democrats, PKB, PKS, and KPPI on the other. In a long period from 2019 to the end of 2021, differences in attitudes have caught the public's attention, especially the people of the Ende Regency. This study uses a descriptive qualitative method that aims to examine the motives behind the differences in the political attitudes of the coalition parties in determining the candidate for Deputy Regent of Ende and how the settlement mechanism is. The results of this study indicate that there are different interest motives from each pole of the coalition party. The pole of the Golkar party translates the position of Deputy Regent of Ende as a position that must be filled by its cadres, which is based on the rationality of political ethics. On the other hand, the six coalition parties also interpret the position of Deputy Regent of Ende as a shared right, which can be filled by all coalition party cadres. Meanwhile, the mechanism for resolving the polemic of differences in attitudes between the two coalition parties is carried out through a voting mechanism and a punishment/penalty mechanism. These two mechanisms are said to be strategies to discipline the behavior of political party elites who tend to maintain their political power and interests.